The red arrow - Brewer, William, 1989- (Alfred A. Knopf, 2022)
"When a once promising young writer agrees to ghostwrite a famous particle physicist's memoir, his livelihood is already in jeopardy: plagued by debt after failing to deliver a novel, he's grown distant from his wife--a successful A.I. researcher--and is haunted by an overwhelming dread he describes as "The Mist." Desperate for relief, he undergoes an experimental, psychedelic treatment and emerges to find his world transformed: joy suffuses every moment. His opportunities are endless. For the first time, he understands himself in a larger, universal context. But when the physicist suddenly disappears, the narrator must track him down in order to finish the project, salvage his new outlook, and finally escape the sense of doom that has always trailed him. Moving swiftly across time and geography--from a chemical spill in West Virginia, to psychedelic therapy in Oakland, to a frecciarossa racing across the Italian countryside--The Red Arrow is a spiraling, spellbinding journey through art, memory, and the contradicting layers that compose the self"--